The Relationship between Anterior Cruciate Ligament Injury and Osteoarthritis of the Knee - David Simon; Randy Mascarenhas; Bryan M. Saltzman; Meaghan Rollins; Bernard R. Bach; Peter MacDonald (Advances in Orthopedics)
Anterior cruciate ligament (ACL) tears are a common injury, particularly in the athletic and youth populations. The known association between ACL injury and subsequent osteoarthritis (OA) of the knee merits a more in-depth understanding of the relationship between the ACL-injured knee and osteoarthritis. ACL injury, especially with concomitant meniscal or other ligamentous pathology, predisposes the knee to an increased risk of osteoarthritis. ACL insufficiency results in deterioration of the normal physiologic knee bending culminating in increased anterior tibial translation and increased internal tibial rotation. This leads to increased mean contact stresses in the posterior medial and lateral compartments under anterior and rotational loading. However, surgical reconstruction of the ACL has not been shown to reduce the risk of future OA development back to baseline and has variability based on operative factors of graft choice, timing of surgery, presence of meniscal and chondral abnormalities, and surgical technique. Known strategies to prevent OA development are applicable to patients with ACL deficiency or after ACL reconstruction and include weight management, avoidance of excessive musculoskeletal loading, and strength training. Reconstruction of the ACL does not necessarily prevent osteoarthritis in many of these patients and may depend on several external variables.